Concepts of transdisciplinary engineering: a transdisciplinary landscape. (29th September 2021) - Lattanzio, S.; Nassehi, A.; Parry, G.; Newnes, L.B.
The term 'transdisciplinary' is receiving increased attention within engineering academic and research funding communities. We survey authors of papers presented at the 27th ISTE International Transdisciplinary Engineering Conference (TE2020) to answer two research questions: 1) How do authors define transdisciplinary engineering? 2) What do authors perceive differentiates interdisciplinary engineering research from transdisciplinary engineering research? Responses from thirty-four participants (50%), are qualitatively analysed. Results show that for the three characteristics commonly used in characterisations of transdisciplinarity (goal, collaboration and integration), multiple concepts exist. These range from generic expressions which overlap with how interdisciplinarity is defined within the general literature, to stronger, more definitive expressions. Conclusions find that rather than a single definition a transdisciplinary landscape exists. To enable users to define where they sit in the transdisciplinary landscape, we create a framework enabling users to map their position under the three key characteristics of goal, collaboration and integration.